Socio-economics of artisanal fishery in Chile - Rosas-Muñoz, Juan Carlos (2020)
This thesis is composed by 5 chapters: Chapter 1 is an introductory frame to characterise the artisanal fishery sector in Chile. Chapter 2 to 4 are research chapters focused on three economic issues related to the artisanal fishery sector. Finally, chapter 5 provides conclusions for the whole thesis. The three research chapters are summarised below. Chapter 2, Optimal harvest decision in a dynamic context: Managing the Territorial Use Rights Fisheries (TURFs) by Chilean Artisanal Organisations. This chapter examines the determinants of the harvesting decisions made by artisanal organisations operating under territorial use rights (TURFs) in the Chilean abalone fishery (locally known as Loco). Although biological gains recovering the benthonic resources are broadly recognised, the effects of specific harvesting decisions on TURFs effectiveness are still little known. This work evaluates harvesting decisions of artisanal organisations accounting for loco's stock and price, harvest, governmental approval quotas, and catchability. In the first part, a theoretical model explores harvesting decisions through a dynamic model for two periods of time. The predictions include a positive effect of higher assigned quotas on harvest and a positive effect on harvest by higher loco's price, stock and catchability. In the second part, a set of data is created from annual reports of artisanal organisations. Then, the predictions of the theoretical model are empirically tested through regressions. The empirical model supports the theoretical predictions found, except for the loco's price effects. The main conclusions support the assumption that there is an interior solution in a dynamic context as well as reinforce the importance of quota and stock as key harvesting decision variables. Some policy guidelines are provided according to such findings. Chapter 3, The effects of Natural Disasters on Multidimensional Poverty in Chile: Differences between fishermen and non-fishermen population. Because natural disasters are commonly associated with important human and economic losses, it is not a surprise to find an extensive international literature focus on poverty and natural disasters nexus. Nevertheless, most of the studies measuring poverty only take into account the Gross Domestic Product or household’s income. Moreover, little is known about the effect of natural shocks within specific population groups over time, especially those who are more socioeconomically vulnerable before the shocks. I contribute by evaluating the impact of the 2010 Chilean earthquake and the later tsunami on households’ multidimensional poverty emphasising short and long-term differences within the overall Chilean population and the artisanal fishery sector. To do so, I account for the unique multidimensional poverty index (MPI) used in Chile for policy purposes which includes four dimensions: housing, work and social security, education and health. I use data from the CASEN survey for calculating a pre-disasters MPI in 2006-2009, short-term effects in 2011 and long-term in 2013. ONEMI database allowed identifying those localities only affected by the earthquake and those also impacted by the later tsunami. I estimate the effect of both disasters on multidimensional poverty for fishermen and non-fishermen using a difference-indifference methodology. The main findings indicate significant differences between fishermen and the overall population. The first group was more affected in the work and social security dimension for both disasters, but especially due to the tsunami in the short and long-term. On the contrary, fishermen showed a quicker recovery in the housing dimension and no significant effects on education. Some policy guidelines are offered for tackling with future disasters in the artisanal sector. I also propose some ways for planning a post-disaster recovery in which fishermen well-being is promoted. Chapter 4, Monitoring in Artisanal Fisheries working under TURFs system, a theoretical approach. This chapter examines the effects of monitoring in fisheries management in combination with regulators for fishermen working in artisanal organisations. I focus on the effects of fines, which are defined by the regulator and/or organisation, to induce compliance with a quota. Recent studies show that the enforcement and compliance decisions under the TURFs regime are particularly relevant for the Chilean case due to illegal fishing. This research evaluates three theoretical models to examine which is the minimum fine to reach the first best to induce compliance of the assigned quota by organisations and fishermen. A first model considers exogenous monitoring in a static version, whereas the second is exogenous monitoring in a dynamic version. A third model accounts for endogenous monitoring in a static version. The results show that the extraction efforts are higher when fishermen work only with the artisanal organisation. Moreover, the regulator's fine is lower and the organisation's fine is higher when fishermen are working together with the organisation and regulator.